Assessing early childhood giftedness in Qatar: A validation study of the Arabic-translated gifted rating scales-preschool form, GRS-P - Ali M. Alodat (22006535) (2025)
This study aims to investigate the psychometric properties of the Arabic-translated Gifted Rating Scales-Preschool/Kindergarten Form (GRS-P) in Qatar. This study translated the GRS-P into Arabic, examined the validity and reliability indicators, and explored gender and age differences in children’s performance on the translated GRS-P. Two hundred thirteen children aged four to six years and sixteen teachers from eight kindergartens in Doha participated in this study. Results revealed strong internal consistency reliability and significant positive correlations between GRS-P subscales, the HOPE Scale, and the Child Developmental Profile. Confirmatory factor analysis results indicated that the one-factor structure across the GRS-P subscales presented varied levels of fit. Gender and grade level analysis showed no significant differences in GRS-P scores. This study contributes to effectively identifying gifted children in Qatar, offering insights for educational practitioners and policymakers. Other Information Published in: High Ability Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13598139.2025.2456301